Simulation of plasma wakefield focusing and self-focusing of a short sequence of electron bunches depending on the bunch length, shape and distance between bunches - Bondar, D.S.; Maslov, V.I.; Onishchenko, I.N. (Problems of Atomic Science and Technology, 2022)
By using two-dimensional numerical simulation, the ratio between the effects of wakefield focusing and self-focusing during the propagation of a short sequence of electron bunches in plasma has been simulated. Cases of dominant wakefield focusing have been demonstrated. In addition, the collection data is presented on the parameters of the bunch length, shape and distance between bunches correspond to certain ratios of wakefield focusing and self-focusing that can be used in further studies.